Baseline Survey for Reproductive Disorders in Indigenous Dairy Animals Reared by Marginal Farmers in Three Districtsof Punjab - Honparkhe, Mrigank; Kumar, Ajeet; Singhal, Sumit; Bisla, Amarjeet; Singh Brar, Parkash; Singh Ghuman , Sarvpreet (The Indian Journal of Animal Reproduction, 2025)
The attainment of maximum production potential from an animal envisages one calf crop per year. However, various reproductive problems are responsible for increasing the inter-calving period for more than 15 months even at the well managed dairy farms. Most of the dairy animals in India as well as in Punjab are reared by small and marginal farmers so, this study was aimed at to prepare baseline data of major reproductive problems in the indigenous dairy animals in three districts (Ludhiana, Bathinda and Tarn taran) of Punjab. A total of 127 villages were covered for completing 3000 households (1000 per district) based on a predesigned questionnaire. It was observed that buffaloes were more reared by all the small and marginal farmers of three districts than indigenous cattle. The average number of total cattle, total buffaloes, adult buffaloes, buffalo heifers as well as total livestock per household varied significantly (p<0.05) among all the three districts. The three major reproductive problems that were encountered after questionnaire analysis from farm ers were observed to be anestrus, delayed puberty and repeat breeding. The incidences (%) of delayed puberty (p<0.01), anestrus (p<0.001), repeat breeding (p=0.009), ante-partum (p<0.001) and post-partum prolapse (p=0.010) were significantly greater in buffaloes as compared to indigenous cows. The baseline data indicated the predominance of infertility problems viz. anestrus, delayed puberty and repeat breeding as compared to peri-partum complications in buffalo and indigenous cattle reared by small and marginal farmers of three major district of Punjab. There is need to sensitize the dairy farmers regarding these reproductive disorders and their timely interventions so as to obtain maximum reproductive and productive potential.